Standing Out While Fitting In: Visual Design of Text Overlays in Social Media Communication - Farace, Stefania; Ordenes, Francisco Villarroel; Herhausen, Dennis; Grewal, Dhruv; Ruyter, Ko de (Journal of Marketing, 2026)
The vast amount of content on social media platforms makes it challenging for firms to create posts that get noticed. An increasingly popular approach to increase customer engagement relies on text overlays, where text is placed directly on images. Such practices raise questions of how to balance the visual and text elements for the best impact. Three key factors, commonly used by practitioners, can trigger engagement because of their visual salience: (1) the degree of dynamism or implied motion in the image as well as the (2) size and (3) centrality of the text overlay. Using multiple methods, including field studies, online experiments, and managerial interviews, the authors establish that a text overlay that is too large and centrally placed, combined with a dynamic image, has negative effects on consumer engagement, because these design combinations make the post visually unappealing. The authors leverage these findings to develop an interactive app that can help managers compose more engaging multimodal social media posts.